Positioning and Rebranding as a State Security Tools in Global Space - Ishchenko, Ihor; Bashkeieva, Olena (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2021)
The purpose of this article is to explore positioning and rebranding as tools for state security in global space, using the methodology of constructivism in international relations. The author hypothesizes that positioning the country as safe will be attractive only if there is a unifying factor based on the principles of consocial democracy. To achieve this purpose, the authors used several scientific approaches and methods: constructivism as a scientific paradigm; dialectical method; content analysis, and comparison. The article covers the following issues: Positioning and rebranding in modern conditions; Level of branding effectiveness in Ukraine; National identity as the basis for rebranding and state security; Rebranding states in the face of new challenges and threats. The essence of the conclusions is as follows: States will choose a partner for economic cooperation under difficult conditions in terms of political risks, benefits, and costs. This trend is about renewed positioning and rebranding to facilitate decisions on cooperation. The effectiveness of the existing state brand depends not only on creating an attractive external picture of the country’s positioning. Without a genuine alignment of the declared brand with the internal situation of the state, the political system as a whole, the congruent of the mental construct of the main political structures and the social environment, the brand will not be attractive to investors and the country will remain in an unstable environment.

Celem artykułu jest zbadanie pozycjonowania i rebrandingu jako narzędzi zapewniających bezpieczeństwo państwa w przestrzeni globalnej przy użyciu konstruktywizmu w stosunkach międzynarodowych. Hipoteza zakłada, że pozycjonowanie kraju jako bezpiecznego byłoby atrakcyjne tylko wtedy, gdy istnieć będzie czynnik jednoczący oparty na zasadach demokracji konsocjonalnej. Aby sprostać temu założeniu, autorzy zastosowali szereg perspektyw i metod naukowych: konstruktywizm jako paradygmat naukowy; metodę dialektyczną; metody analizy treści i porównawczą. W artykule omówiono następujące kwestie: pozycjonowanie i rebranding w nowoczesnych warunkach; poziom skuteczności brandingu na Ukrainie; tożsamość narodowa jako podstawa rebrandingu i bezpieczeństwa państwa; rebranding państw w obliczu nowych wyzwań i zagrożeń. Wnioski są następujące: państwa wybierają partnera do współpracy gospodarczej w trudnych warunkach, szacując ryzyko polityczne, korzyści i koszty. Trend ten polega na aktualizacji pozycjonowania i rebrandingu w celu ułatwienia podejmowania decyzji o współpracy. Skuteczność istniejącego brandu państwowego zależy nie tylko od stworzenia atrakcyjnego zewnętrznego pozycjonowania kraju. Bez prawdziwego dostosowania deklarowanego brandu do faktycznego statusu państwa, jego systemu politycznego jako całości, a także głównych struktur politycznych i środowiska społecznego, brand nie będzie atrakcyjny dla inwestorów, a państwo pozostanie w niestabilnym środowisku.
Pozycjonowanie i rebranding jako narzędzia bezpieczeństwa państwa w przestrzeni globalnej
Keywords: positioning; rebranding; security; international relations; constructivism; identity; values; interests; pozycjonowanie; rebranding; bezpieczeństwo; stosunki międzynarodowe; konstruktywizm; tożsamość; wartości; interesy